Verdoorn law - a retrospective view - Bradley, John; Prendergast, Canice (Economic & Social Studies, 1986)
We examine the origins of the Verdoorn law and the key role it plays in Kaldor's growth analysis. We suggest that two empirical studies of the Irish economy (Kennedy, 1971 and Kennedy and Dowling, 1975) can be interpreted within a Kaldorian framework. We contrast this framework with the alternative methodology based on the neo-classical theory of the firm and suggest that the latter may have provided a better picture of how economies hit by the supply shocks of the 1970s reacted to those shocks. Finally, we illustrate how Verdoorn `type? laws can be derived using the neo-classical approach.
Keywords: Verdoorn law; Kaldor's growth analysi